2021
DOI: 10.5194/angeo-39-31-2021
|View full text |Cite
|
Sign up to set email alerts
|

Testing the electrodynamic method to derive height-integrated ionospheric conductances

Abstract: Abstract. We have used empirical models for electric potentials and the magnetic fields both in space and on the ground to obtain maps of the height-integrated Pedersen and Hall ionospheric conductivities at high latitudes. This calculation required use of both “curl-free” and “divergence-free” components of the ionospheric currents, with the former obtained from magnetic fields that are used in a model of the field-aligned currents. The second component is from the equivalent current, usually associated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Although the fact that the nightside aurora can modulate ionospheric conductivity has previously been recognized (Shue et al., 2001, e.g. ), measuring the aurora‐induced conductivity has proven to be exceedingly difficult (Weimer & Edwards, 2021). Our results indicate that electron precipitation from the diffuse and discrete aurora are strongly enhancing E‐region conductance, causing widespread irregularity dissipation in the local winter auroral region.…”
Section: Discussionmentioning
confidence: 99%
“…Although the fact that the nightside aurora can modulate ionospheric conductivity has previously been recognized (Shue et al., 2001, e.g. ), measuring the aurora‐induced conductivity has proven to be exceedingly difficult (Weimer & Edwards, 2021). Our results indicate that electron precipitation from the diffuse and discrete aurora are strongly enhancing E‐region conductance, causing widespread irregularity dissipation in the local winter auroral region.…”
Section: Discussionmentioning
confidence: 99%
“…The B y ‐dependence of electron precipitation implies a similar B y ‐dependence of ionospheric conductance. Recent studies (Holappa et al., 2021 ; Weimer & Edwards, 2021 ) have indeed found a similar IMF B y ‐dependence of ionospheric conductance, maximizing in the dawn sector.…”
Section: Introductionmentioning
confidence: 72%
“…The B y -dependence of electron precipitation implies a similar B y -dependence of ionospheric conductance. Recent studies (Holappa et al, 2021;Weimer & Edwards, 2021) have indeed found a similar IMF B y -dependence of ionospheric conductance, maximizing in the dawn sector.…”
mentioning
confidence: 68%